A multicenter study on rates and risk factors of proliferative vitreoretinopathy in a low-income economy - Ogugua Ndubuisi Okonkwo; Martha-Mary Udoh; Olukorede Adenuga; Wilson Ovienria; Affiong Ibanga; Dennis Nkanga; Idris Oyekunle; Toyin Akanbi; Chineze Agweye (PLoS ONE, 2025)
Objective To assess the rate and identify risk factors for proliferative vitreoretinopathy (PVR) in Nigerian patients with rhegmatogenous retinal detachment (RRD). Methods and analysis Multicenter, prospective, cross-sectional study of consecutive RRD patients attending four ophthalmic clinics, recruited over a period of twelve months. Biodata, presenting complaints, symptom duration, best corrected visual acuity, extent of RRD, status of macular attachment, presence, and grade of PVR and fellow eye were assessed. Data was analyzed using SPSS version 22 (Pearson Chi-Square test, Mann-Whitney U test, Fisher’s Exact test, and logistic regression analysis). Results 154 of 174 eyes with RRD were included in the final analysis, and 53/154 (34.4%) developed PVR. Twenty eyes (11.5%) had media opacity, and detailed retinal examination was not possible (diagnosed via B-scan ultrasound). 154 RRD was analyzed. Therefore, the rate of all PVR was53/154 (34.4%). Grades of PVR: Grade D: 27 eyes (50.9%), Grade C: 19 eyes (35.9%), Grade B: 5 eyes (9.4%), and Grade A: 2 eyes (3.8%). The rate of advanced PVR grades D + C is 46/154 (29.8%). Forty-six of 53 PVR eyes (86.6%) had vision 3/60 or less (p < 0.001). Risk factors associated with PVR were extremes of age, i.e., < 25 and >66 years (especially older age (>66 years)), previous intraocular surgery, longer symptom duration, and RD features including 4-quadrant involvement, total RD, macular involvement by RD, and presence of fellow eye RD. Gender, Myopia, and trauma were not risks for PVR. Conclusion Previous reports of PVR rates in Nigerians may have been underestimated. A multi-pronged approach, including research into adjuvant pharmacotherapy, can reduce PVR rates and improve treatment outcomes.